Late Cenozoic cooling and evolution history of the Kangmar dome in southern Tibet: Insights from inverse thermal modeling - Ma, Zining; Han, Zhongpeng; Li, Yalin; Xu, Tiankun; Han, Xu; Bi, Wenjun; Zhang, Wenzhong (Frontiers in Earth Science, 2023)
The North Himalayan Gneiss Domes, which are essential parts of the Cenozoic extensional structures in Southern Tibet, record the thermal and tectonic processes that occurred after the India-Asian collision and are thought to be effective structures regulating post-collision intracontinental deformation. However, it is still unclear how these domes are formed and how they contribute to the regulation process. Here, we performed detailed geological mapping, elevation transect sampling, low-temperature thermochronological testing, and 3D modeling on the Kangmar dome, which is located west of the N‒S treading Yadong-Gulu rift, and its core-cover contact fault is suspected to be the northern continuation of the South Tibetan Detachment System (STDS). Our analysis revealed a discrepancy in the deformation histories of the dome’s northern and southern portions. We proposed a model in which the core-cover contact fault of the Kangmar dome was a part of the STDS and the doming event that occurred at ~12.2 Ma was dominated by thrust stacking of the southward mid-crustal channel flow. The rapid cooling following the middle Miocene was possibly influenced by the N‒S Trending Yadong-Gulu rift activity. The present landscape was shaped by the incision of the Nianchu River, which was accompanied by increased glacial activity during the Pleistocene. Our findings enhance the intracontinental deformation patterns following collisions and shed light on the numerous domes in Himalayas and other orogenic belts.